2015
DOI: 10.1103/physreva.91.023619
|View full text |Cite
|
Sign up to set email alerts
|

Dark-bright solitons and their lattices in atomic Bose-Einstein condensates

Abstract: I n the present contribution, we explore a host of different stationary states, namely dark-bright solitons and their lattices, that arise in the context of multicomponent atomic Bose-Einstein condensates. The latter are modeled by systems of coupled Gross-Pitaevskii equations with general interaction (nonlinearity) coefficients gy. It is found that in some particular parameter ranges such solutions can be obtained in analytical form, however, numerically they are computed as existing in a far wider parametric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 34 publications
6
36
0
Order By: Relevance
“…We therefore checked the dynamical stability of the stationary dark-bright soliton state. In accordance with the results of [38], we found there is some instability but nevertheless the corresponding growth rate is rather small, i.e., small enough that over the time scales reported herein, the resulting weak dynamical instabilities (of stationary states) have not yet set in. Our detailed examination of this feature suggests that during the intermediate, as well as disordered phase dynamics, the collisional dynamics may develop high amplitudes, thus rendering some of the bright solitons less visible in the space-time plots of e.g.…”
Section: B Dark-bright Solitonssupporting
confidence: 92%
See 2 more Smart Citations
“…We therefore checked the dynamical stability of the stationary dark-bright soliton state. In accordance with the results of [38], we found there is some instability but nevertheless the corresponding growth rate is rather small, i.e., small enough that over the time scales reported herein, the resulting weak dynamical instabilities (of stationary states) have not yet set in. Our detailed examination of this feature suggests that during the intermediate, as well as disordered phase dynamics, the collisional dynamics may develop high amplitudes, thus rendering some of the bright solitons less visible in the space-time plots of e.g.…”
Section: B Dark-bright Solitonssupporting
confidence: 92%
“…A few examples of both in-phase and outof-phase DBS stationary states are shown in Figure 2 and 3 respectively. The few DBS states are in line with the states reported in [28], while a discussion of DBS consisting of many waves and possible analytical DBS-lattice solutions based on elliptic functions are given in [38].…”
Section: B Identification and Continuation Of Stationary Dbs Statessupporting
confidence: 59%
See 1 more Smart Citation
“…In the 1D case studied in Ref. [48], it has been observed that the stability of the individual dark-bright solitons is not dramatically affected by the variation of σ 12 . Similar findings are observed in the present 2D case, although the instability growth rates start decreasing, resulting in a small stability region close to the upper bound of the examined window of σ 12 (see the bottom panel of Fig.…”
Section: B Numerical Resultsmentioning
confidence: 96%
“…The dark-bright soliton solutions to the Manakov model are given by [204] , , where E B = a 2 /2 is the 'binding energy' of the bright component [204] . If the coupling strengths are tuned away from the integrable point, it is sometimes possible to find closed form dark bright solitary wave solutions [204,242,244,245] . However, in most parameter regimes solutions must be found numerically [191] .…”
Section: Methodsmentioning
confidence: 99%